Optimalisasi media teknologi dalam pembelajaran ips untuk meningkatkan keaktifan belajar siswa di mts bahrul ulum tambakberas jombang - DZIKRULLOOH, RAHMANIA RAMADHANI (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the utilization of technological media in Social Studies (IPS) learning at MTs Bahrul Ulum Tambakberas Jombang and its impact on students’ learning engagement. The background of this research is the limited use of available technological facilities such as computer laboratories and auditoriums. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that the use of technological media in teaching is still suboptimal, as teachers mainly rely on lectures and student worksheets. However, when interactive media such as educational videos and digital simulations are used, a significant increase in student engagement is observed. This study is limited to a single madrasah and focuses only on Social Studies subjects; therefore, the findings cannot be generalized to all schools or madrasahs. Nevertheless, this research provides valuable insights into the challenges and potential of integrating technology in contextual learning at pesantren based madrasah.